Why Jury Duty Matters : a Citizen's Guide to Constitutional Action. - Ferguson, Andrew Guthrie (NYU Press, 2012)
"It's easy to forget how important the jury really is to America. The right to be a juror is one of the fundamental rights guaranteed to all eligible citizens. The right to trial by jury helped spark the American Revolution, was quickly adopted at the Constitutional Convention, and is the only right that appears in both the Constitution and the Bill of Rights. But for most of us, a jury summons is an unwelcome inconvenience. Who has time for jury duty? We have things to do. In Why Jury Duty Matters, Andrew Guthrie Ferguson reminds us that whether we like it or not, we are all constitutional actors. Jury duty provides an opportunity to reflect on that constitutional responsibility. Combining American history, constitutional law, and personal experience, the book engages citizens in the deeper meaning of jury service. Interweaving constitutional principles into the actual jury experience, this book is a handbook for those Americans who want to enrich the jury experience. It seeks to reconnect ordinary citizens to the constitutional character of a nation by focusing on the important, and largely ignored, democratic lessons of the jury. Jury duty is a shared American tradition. It connects people across class and race, creates habits of focus and purpose, and teaches values of participation, equality, and deliberation. We know that juries are important for courts, but we don't know that jury service is important for democracy. This book inspires us to re-examine the jury experience and act on the constitutional principles that guide our country before, during, and after jury service"--Publisher's description.